The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18488/journal.68.2019.62.169.179
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Farmers Knowledge and Safety Practices towards Pesticides: Results from Field Observation in Southeastern DR Congo

Abstract: Contribution/Originality: This study is one of the very few studies which have investigated the misuse of pesticides in Lubumbashi. Results highlighted poor handling practices of pesticides by farmers and limited knowledge of protective equipment and weather conditions while using plant protection products. serious health issues arising from the exposure while mixing, spraying pesticides and working in treated fields [5-8]. For many farmers, the situation has been exacerbated because of the lack of protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(41 reference statements)
0
3
0
2
Order By: Relevance
“…While some farmers reported washing their hands with soap (16.6%), 24% washed their hands with only water. This behavior is typical among farmers in various agricultural landscapes despite their awareness of the potential danger of pesticides, indicating a lack of necessary precautions to minimize risks (Atreya, 2007; Balasha et al, 2019; Nafissa et al, 2020)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While some farmers reported washing their hands with soap (16.6%), 24% washed their hands with only water. This behavior is typical among farmers in various agricultural landscapes despite their awareness of the potential danger of pesticides, indicating a lack of necessary precautions to minimize risks (Atreya, 2007; Balasha et al, 2019; Nafissa et al, 2020)…”
Section: Resultsmentioning
confidence: 99%
“…The findings indicated that farmers are aware of the crucial protective equipment necessary for safe pesticide use. Despite this knowledge, various factors, such as low purchasing power, risk minimization, discomfort while working with PPE, negligence, and unavailability in local markets, prevent farmers from acquiring and utilizing such equipment (Ajayi & Akinnifesi, 2007; Balasha et al, 2019). Farmers’ attitudes and behavior while and after applying pesticides can expose them to the risks of pesticides as they may not be aware of the potential health risks associated with pesticide exposure, leading to a lack of concern for their own safety when handling these chemicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…À l'aide d'un questionnaire semi-structuré, les entretiens individuels avec les maraîchers ont porté trois points : (1) les caractéristiques socio-économiques des agriculteurs (niveau d'instruction, âge, surfaces cultivées, importance accordée à la production maraîchère, cultures pratiquées) ; (2) les dégâts observés et les pratiques phytosanitaires (facteurs déclenchant du traitement, coût des pesticides, type de produits utilisés et déterminants de leur choix, ainsi que mode d'emploi, moyens de protection utilisés et gestion des emballages) ; (3) la perception des agriculteurs des risques sanitaires (problèmes ressentis après l'application des pesticides). Ces entretiens avec les maraîchers ont été complétés par des observations directes lors de la préparation des bouillies et de l'application des pesticides ; ces deux étapes sont cruciales en termes d'exposition au risque car, d'une part, les agriculteurs sont en contact avec les produits concentrés et dilués (Schiffers, 2011 ;Gouda et al, 2018) et d'autre part, c'est le moment où la qualité des matériels utilisés et le comportement ainsi que l'attitude des agriculteurs sont correctement évalués (Schiffers, 2011 ;Mushagalusa et al, 2019).…”
Section: Enquêtes Auprès Des Agriculteurs Et Des Vendeurs Des Pesticidesunclassified
“…La raison principale donnée par les interviewés pour le non-port des équipements de protection est le manque d'argent pour s'en procurer. La même raison a été avancée par les agriculteurs urbains du Togo et de Lubumbashi où respectivement Kanda et al (2013) et Mushagalusa et al (2019) ont également évoqué la négligence des pratiques d'hygiène, c'est-à-dire se laver le corps, ou au moins les mains après le traitement. Cette négligence, associée à des imprudences observées, telles que manger et fumer pendant le traitement, accroît significativement les risques d'intoxication, de brûlures et dans les cas extrêmes, peut conduire à la mort (Schiffers, 2011 ;Zikankuba et al, 2019 ;Lekei et al, 2020).…”
Section: Typologie Des Pesticides Choix Et Pratiques Aggravant Les Ri...unclassified